Novel ionic surface imprinting technology: design and application for selectively recognizing heavy metal ions. Issue 5 (18th January 2019) - An, Fu-Qiang; Li, Hu-Fei; Guo, Xu-Dong; Gao, Bao-Jiao; Hu, Tuo-Ping; Gao, Jian-Feng
Abstract : SIPs have good chemical stability and reusability. They could be reused without a significant reduction in adsorption capacity and selectivity coefficient. Abstract : Traditional bulk polymerization imprinted technology and existing surface imprinted technology have some congenital defects. Therefore, it is necessary to design more efficient surface imprinted technology. In this paper, novel surface imprinting technology with higher imprinting efficiency is well designed. It fully realizes the synchronization of polymer crosslinking and template imprinting. Then the surface imprinted polymers (SIPs) are synthesized using metal ions as a template. The physicochemical characteristics of the SIPs are characterized by scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET) studies, Fourier transform infrared spectroscopy (FTIR) and elemental analysis. The adsorption performances and recognition selectivity of the SIPs towards the template are investigated by a batch method. The experimental results show that the SIPs possess excellent adsorption ability and selectivity towards the template. The selectivity coefficients of the SIPs prepared in this study are higher than those of IIPs prepared by other imprinting methods. The adsorption process could be well described by the Lagergren-first-order model and Langmuir monolayer chemical adsorption. The SIPs have good chemical stability and reusability. Consecutive adsorption–desorption experiments show that the exhausted SIPs could be effectively regenerated, and the regenerated SIPs could be reused without a significant reduction in adsorption capacity or selectivity coefficient.